(untitled) (Bangladesh Journal of Botany, 2018)
Egg masses and females of Meloidogyne incognita from a tomato (Lycopersicon esculentum Mill. cv. Falcon) field from Central Anatolia of Turkey, were collected and examined for the presence of fungi. Of the 138 egg masses of M. incognita 35.5% were colonized by one or more of 9 species of genera Arthrobotrys, Cylindrocarpon, Fusarium, Paecilomyces, Plectosphaerella, Rhizoctonia and Verticillium while 31.8% of the 138 females were colonized by 6 species, from the same genera except Paecilomyces and Plectosphaerella. Fusarium oxysporum was by far the predominant species in both the egg masses and females of M. incognita.